The fluvial history of the lower Vaal River catchment - Gibbon, Ryan James (My University, 2009)
Cosmogenic nuclide burial dating was used to determine the age of ancient alluvial terrace deposits in the lower Vaal River catchment, and thus provide an absolute fluvial chronology. A poor chronological framework has been the primary shortcoming of previous fluvial history studies as there was no accurate way to evaluate or correlate the proposed driving mechanisms with the fluvial events themselves. Cosmogenic nuclide burial dating has shown that there have been three periods, each of both river incision and alluvial gravels and fines aggradation, in the Pliocene. Burial dating determined that periods of bedrock incision have occurred relatively rapidly over short periods of time, following lengthy periods of net aggradation. It has been proposed that the lower Vaal River catchment provided the ideal situation for rapid bedrock incision to pro- ceed sporadically. The Vaal River in its lower reaches is largely confined to pre-Karoo valleys that are filled with soft, easily erodible Karoo rocks. When these rocks are at least partially exposed along the river channel/valley, rapid bedrock erosion and incision occurs through the action of saltating resistant clasts abrading the channel. It has been argued that these incision events oc- cur only when suitable climatic conditions develop that allow for the complete erosion of alluvial gravel deposits lining the Vaal River channel/valley (i.e. fre- quent and large formative discharges are needed to achieve this). Periods of gravel aggradation have been attributed to an increase in coarse sediment sup- ply, primarily through the erosion of older alluvial deposits in the valley during periods of reduced vegetation cover. Periods of fine sediment aggradation are the net result of a reduction in the capacity of formative discharges, a direct result of a drying climate. It is thus apparent that climate change has played the most important role in controlling the fluvial evolution of the Vaal River. Climate controls fluvial events by determining the Vaal River’s net transport ability. Various combinations of changes in transport and erosion potentials, in both the river and surrounding landscape, have resulted in varying fluvial outcomes. In conclusion, the fluvial evolution of the lower Vaal River catch- ment is unique due to a number of aspects. The structure of the pre-Karoo surface and readily available resistant clasts from older terrace deposits and tillite, in conjunction with climate change, have proved crucial in shaping the Vaal River’s fluvial history.